Effectiveness of cognitive behaviour therapy on depression among haemodialysis patients: a systematic review of literature - Ahmad Othman, Akmarina; Wan Jaafar, Wan Marzuki; Zainuddin, Zaida Nor; Mohamad Yusop, Yusni; Cerniglia, Luca (Cogent OA, 2020)
End-stage renal disease (ESRD) is a major public health issue in Malaysia and worldwide. Depression is highly associated with ESRD and with the increasing number of ESRD, the rate of depression will also grow. There are limited data on clinical trials of antidepressant medication on ESRD due to safety reasons. Due to that, psychological intervention is a preferred treatment for this population. Previously, studies on the effectiveness of cognitive behaviour therapy (CBT) have been focused more on patients with depression with no comorbid chronic medical illness. Therefore, the present article is set out to analyse the existing literature on the effectiveness of CBT on depression among ESRD undergoing haemodialysis treatment. Guided by the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) review method, a systematic review on Scopus database has identified 10 studies. Further review of these articles resulted in two main themes—single-group trial and two-groups trial. The two-groups trial is further producing another two sub-themes. The discussion is mainly on the lack of randomized trial in the depression treatment among haemodialysis patients in Malaysia. Several recommendations are being highlighted, where are to compare CBT treatment group with another active therapy and to use more than one database for the research searching tools.